THE ROLE OF WORK CULTURE, WORK MOTIVATION, WORK ENVIRONMENT AND COMPETENCE IN INFLUENCED EMPLOYEE PERFORMANCE IN ARGOMULYO DISTRICT, SALATIGA CITY - Ponco Margono Hasan; Mada Adi Wibowo; Hardi Utomo; Erna Sudarmawanti (Edusight International Journal of Multidisciplinary Studies, 2025)
This study aims to find out the simultaneous influence of work culture, work motivation, work environment, and competence in influenced employee performance in Argomulyo District, Salatiga City, both partially and simultaneously. Population of the study was 68 workers in Argomulyo District. This research method was explanatory, and the data analysis methods used were validity testing, reliability testing, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination tests. Based on the t-test and F-test, it was found that both the partial and simultaneous too for influence of work culture, work motivation, work environment, and competence on employee performance were hypothesized to be accepted. The magnitude of the influenced of work culture (X1), work motivation (X2), work environment (X3), and competence (X4) simultaneously or collectively on employee performance (Y) in Argomulyo District is evidenced by the Adjusted R Square that value of 0.549, which means that X1, X2, X3, and X4 simultaneously influenced employee performance (Y) by 54.9%, while the remain 45.1% is influence by other variables.